If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 65 = (3 + -1l) * w Reorder the terms for easier multiplication: 65 = w(3 + -1l) 65 = (3 * w + -1l * w) Reorder the terms: 65 = (-1lw + 3w) 65 = (-1lw + 3w) Solving 65 = -1lw + 3w Solving for variable 'l'. Move all terms containing l to the left, all other terms to the right. Add 'lw' to each side of the equation. 65 + lw = -1lw + lw + 3w Combine like terms: -1lw + lw = 0 65 + lw = 0 + 3w 65 + lw = 3w Add '-65' to each side of the equation. 65 + -65 + lw = -65 + 3w Combine like terms: 65 + -65 = 0 0 + lw = -65 + 3w lw = -65 + 3w Divide each side by 'w'. l = -65w-1 + 3 Simplifying l = -65w-1 + 3 Reorder the terms: l = 3 + -65w-1
| 6m-2+m^2+3=56 | | r=3(9t-4) | | 5(3x-4)-3x-2=4 | | 5p-12+2p=6+3p-11 | | n^2+7n-18=0 | | 6(3-2x)+8x=9 | | (5y+4)(y+6)=-4(5y+4) | | -1=5x^2-9x+2 | | 2n-12=53 | | -96+2x=-8x+34 | | 108x^2+63xy+9y^2= | | c(q)6000+10qR(q)=12q | | 8x-9(x+1)=3(5-x) | | d=3e | | 8x=5x+4+5 | | C(q)=600+10q | | x^4-31x^2-180=0 | | 2x+9x-2=33 | | -y+6+3y=-5+y | | -12=-2h+.2(20-6h) | | 5x-71=x+41 | | 4p+21=11p | | 3x+6x-4=4-6 | | 3(2x+1)+4x=43 | | -x-2x-4=3 | | x-4*2x=240 | | 15-(3-4x)=2(y+2) | | (2x-4)x=240 | | 6x^2+3=5x | | x^2-10x-18=0 | | 3(2x+3)+4=-59 | | 8x-2y=-44 |